2016
DOI: 10.18632/oncotarget.10478
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of 14-3-3σ sensitizes mice to DMBA/TPA-induced papillomatosis

Abstract: The p53-inducible cell cycle regulator 14-3-3σ exhibits tumor suppressive functions and is highly expressed in differentiating layers of the epidermis and hair follicles. 14-3-3σ/SFN/stratifin is frequently silenced in human epithelial cancers, and experimental down-regulation of 14-3-3σ expression immortalizes primary human keratinocytes. In the repeated-epilation (ER) mouse model, a heterozygous nonsense mutation of 14-3-3σ causes repeated hair-loss, hyper-proliferative epidermis, and spontaneous development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The exclusive homodimerization critically contributes to the ability of 14-3-3s to inhibit cell proliferation in the presence of other 14-3-3 family members, which are often highly expressed (6). More recently, we demonstrated that 14-3-3s-deficiency in mice leads to an increased frequency and size of DMBA/12-O-tetradecanoylphorbol-13-acetate (TPA)-induced papilloma (7).…”
Section: Introductionmentioning
confidence: 99%
“…The exclusive homodimerization critically contributes to the ability of 14-3-3s to inhibit cell proliferation in the presence of other 14-3-3 family members, which are often highly expressed (6). More recently, we demonstrated that 14-3-3s-deficiency in mice leads to an increased frequency and size of DMBA/12-O-tetradecanoylphorbol-13-acetate (TPA)-induced papilloma (7).…”
Section: Introductionmentioning
confidence: 99%
“…To response the DNA damage, SFN often plays a role in inhibiting DNA errors during mitosis [4,5]. Generally, SFN is expressed at low levels on the nervous and reproductive systems, including in the cortex, retina, placenta, and ovary [6]. Nevertheless, SFN has been reported to be a novel biomarker in various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Er model, it has been shown that stratifin regulates proliferation and differentiation by changing transcription factor YAP1 localization by binding to YAP1 and facilitating nuclear transcriptional function [40]. Intriguingly, a recently generated mouse model with Cre-mediated stratifin depletion did not show significant epidermis defects, suggesting that the Er model may not entirely recapitulate the effects of stratifin ablation [41]. Further experiments will be needed to resolve the contradiction between the two models and clarify the role of stratifin in skin development.…”
Section: Molecular Mechanisms Regulating Skin Developmentmentioning
confidence: 99%